AUDIT QUALITY, COMPANY SIZE, LEVERAGE AND TAX AGGRESSIVENESS: A STUDY ON MANUFACTURING COMPANIES IN 2015-2019 - Suyanto, Suyanto; Alfiani, Hani; Abinowo, Agaphe Christian (Jurnal Perilaku dan Strategi Bisnis, 2023)
The purpose of this study is to demonstrate audit quality, firm size, and leverage of aggressive taxation. This type of research is quantitative secondary data research using the company's annual report on the Indonesia Stock Exchange in 2015-2019. Data collection method using purposive sampling technique resulted in 182 sample data from 49 companies. The data analysis of this research was conducted using descriptive statistical test, classical assumption test, and and multiple linear regression tests. Result show that qualified auditors are able to identify and analyze any possible fraud by the company. In larger companies they have more resources to consider the best policy. In addition, businesses with higher levels of debt tend to have plans to cut back on their significant tax liabilities. The conclusion of this study show that audit quality has no effect on tax aggressiveness, firm size has a negative effect on tax aggressiveness, and leverage has a positive effect on tax aggressiveness.